Optimiztion of PCR reaction conditions for detection M235Tpolymorphism of Angiotensinogen gene in hypertensive patients - يوسف, ميس; فيصل رضوان; هيثم يازجي; إياس الخير (Latakia University Journal -Medical Sciences Series, 2024)
Background: Polymerase chain reaction (PCR) is a sensitive and expensive procedure, and its success requires many attempts. This study aims to develop optimization strategies to amplify a specific sequence in the AGT gene, to detect the M235T polymorphism associated hypertension. Materials and methods: Genomic DNA was extracted by column method, and the PCR reaction was carried out using special primers, applying different conditions, and PCR products were detected using agarose gel electrophoresis. Results: The optimized thermal cycler conditions for PCR reaction were: initial denaturation (temperature 94 °C, for 2 minutes), denaturation (94 °C, 30 seconds, 30 cycles), annealing (60 °C, 30 seconds, 30 cycles), elongation (72°C, 30 seconds, 30 cycles), final elongation (72°C, 5 minutes). The optimized concentrations and volumes of reagents were as follows: master mix (10 μl), forward and reverse primer (3.5 μl of each at a concentration of 21 pmol), DNA template (2 μl at a concentration of 30-50 ng ⁄ μl). Conclusion: Adjusting the annealing temperature, primer concentration, and thermal cycler conditions had the greatest role in adjusting the PCR conditions, and there was no need to make adjustments to the concentrations of other reagents, nor to use additional amounts of magnesium chloride or other additives to enhance the reaction.